Kajian Optimalisasi Sistem Pengangkutan Sampah di Kecamatan Subang, Kabupaten Subang - Shabilla Zahira Shafa; Ira Safitri Darwin (UNISBA Press, 2022)
Abstract. Subang Regency is one of the regencies in West Java that is emergency because the accumulation of waste exceeds the disposal capacity, this is because the transportation system is not yet optimal. The accumulation of garbage in the city center (Subang sub-district) started when the Panembong TPA was closed and the waste had to be disposed of at the Jalupang TPA which is further away from the Panembong TPA. The targets of this research are 1) to identify the existing condition of waste transportation, 2) to identify the optimum number of cycles required and 3) to identify the route of waste transportation in Subang District, Subang Regency. In this research, a study of waste transportation will be carried out using an empirical approach and mix methods. The study was conducted to optimize the waste transportation system with field data obtained through observation, interviews and secondary data, with 3 samples of existing dump trucks using the stationary container system (SCS) calculation method. The results showed that the existing fleet of waste transporters in Subang District as many as 12 fleets of dump trucks and 7 arm rolls can transport about 34.5 tons/day with an average of 1 cycle/day. Meanwhile, the average waste generated per day is 77.66 tons/day. Based on the results of the optimization of waste transportation, the current number of vehicles is sufficient if additional routines, vehicle maintenance and changes to transportation routes are made using the shortest route. So if done the amount of waste transported can reach the target of the generated waste. Abstrak. Kabupaten Subang menjadi salah satu kabupaten di Jawa Barat yang darurat karena penumpukan sampah nya melebihi kapasitas pembuangan, hal tersebut disebabkan belum optimalnya sistem pengangkutan. Menumpuknya sampah di pusat kota (Kecamatan Subang) dimulai ketika TPA Panembong ditutup dan sampah harus dibuang ke TPA Jalupang yang jaraknya lebih jauh dari TPA Panembong. Sasaran pada penelitian ini yaitu 1) teridentifikasinya kondisi eksisting pengangkutan sampah, 2) teridentifikasinya jumlah ritasi optimum yang dibutuhkan dan 3) teridentifikasinya rute pengangkutan sampah di Kecamatan Subang Kabupaten Subang. Dalam penelitian ini akan dilakukan kajian terhadap pengangkutan sampah dengan menggunakan metode pendekatan empiris dan mix methods. Penelitian dilakukan untuk mengoptimalkan sistem pengangkutan sampah dengan data dilapangan yang didapatkan melalui observasi, wawancara dan data sekunder, dengan 3 sampel kendaraan dump truck yang ada menggunakan metode perhitungan stationary container system (SCS). Hasil penelitian menunjukan jumlah armada pengangkut sampah eksisting di Kecamatan Subang sebanyak 12 armada dump truck dan 7 arm roll dapat mengangkut sekitar 34,5 ton/harinya dengan rata-rata ritasi 1 rit/hari. Sedangkan rata-rata timbulan sampah yang dihasilkan per hari sebesar 77,66 ton/hari. Berdasarkan hasil analisis optimalisasi pengangkutan sampah, jumlah kendaraan saat ini sudah memadai jika dilakukan penambahan rit, maintenance kendaraan dan perubahan rute pengangkutan dengan menggunakan rute terpendek. Maka jika dilakukan jumlah sampah yang terangkut bisa mencapai target dari timbulan sampah yang dihasilkan.